Effete-mediated degradation of Cyclin A is essential for the maintenance of germline stem cells in Drosophila. - Chen, D.; Wang, Q.; Huang, H.; Xia, L.; Jiang, X.; Kan, L.; Sun, Q.; Chen, D. (Development, 2009)
Increasing evidence supports the idea that the regulation of stem cells requires both extrinsic and intrinsic mechanisms. However, much less is known about how intrinsic signals regulate the fate of stem cells. Studies on germline stem cells (GSCs) in the Drosophila ovary have provided novel insights into the regulatory mechanisms of stem cell maintenance. In this study, we demonstrate that a ubiquitin-dependent pathway mediated by the Drosophila eff gene, which encodes the E2 ubiquitin-conjugating enzyme Effete (Eff), plays an essential role in GSC maintenance. We show that Eff both physically and genetically interacts with dAPC2, a key component of the anaphase-promoting complex (APC), which acts as a multisubunit E3 ligase and plays an essential role in targeting mitotic regulators for degradation during exit from mitosis. This interaction indicates that Eff regulates the APC/C-mediated proteolysis pathway in GSCs. Moreover, we show that expression of a stable form of Cyclin A, but not full-length Cyclin A, results in GSC loss. Finally we show that, in common with APC2, Eff is required for the ubiquitylation of Cyclin A, and overexpression of full-length Cyclin A accelerates the loss of GSCs in the eff mutant background. Collectively, our data support the idea that Effete/APC-mediated degradation of Cyclin A is essential for the maintenance of germline stem cells in Drosophila. Given that the regulation of mitotic Cyclins is evolutionarily conserved between flies and mammals, our study also implies that a similar mechanism may be conserved in mammals.